NUWT: JAWI-SPECIFIC BUCKWALTER CORPUS FOR MALAY WORD TOKENIZATION (Journal of Information and Communication Technology, 2016)
This paper describes the design and creation of a monolingual parallel corpus for the Malay language written in Jawi. This paper proposes a new corpus called the National University of Malaysia Word Tokenization (NUWT) corpora To the best of our knowledge, currently, there is no sufficiently comprehensive, well-designed standard corpus that is annotated and made available for the public for the Jawi script corpora. This corpus contains the Jawi-specific Buckwalter character code and can be used to evaluate the performance of word tokenization tasks, as well as further language processing. The objective of this work is to conform and standardize the corpora between similar characters in Jawi. It consists of three subcorporas with documents from different genres. The gathering and processing steps, as well as the definition of several evaluation tasks regarding the use of these corpora, are included in this paper. One of the important roles and fundamental tasks of the corpus, which is the tokenization, is also presented in this paper. The development of the Malay language tokenizer is based on the syntactic data compatibility of Malay words written in Jawi. A series of experiments were performed to validate the corpus and to fulfill the requirement of the Jawi script tokenizer with an average error rate of 0.020255. Based on this promising result, the token will be used for the disambiguation and unknown word resolution, such as out-of-vocabulary (OOV) problem in the tagging process.